Unexpected long-term survival of Stage IV pancreatic cancer patient with synchronic liver metastases after multimodal therapy including upfront surgery. Issue 1 (10th January 2023) - Obed, Aiman; Siyam, Mahmoud; Jarrad, Amr Anwar; Abdelhadi, Ody; Ababneh, Muaweih; Annab, Hassan; Füzesi, Laszlo; Bashir, Abdalla; Jarrad, Anwar
Abstract: We report the case of a 56-year-old male with pancreatic cancer and 25 liver metastases. The patient underwent a distal pancreatectomy with 11 metastasectomies in the left liver lobe. Histological examination demonstrated a moderately differentiated ductal adenocarcinoma with pT3N0M1, Stage IVb. Three weeks later, we performed transarterial chemoembolization for the right lobe of the liver, and after 6 weeks we started systemic chemotherapy with FOLFIRINOX. After 31 months, computer tomography examination showed increases in size of the remaining lesions at segment VII/VIII of the right lobe. All liver metastases were surgically removed and a new chemotherapy was initiated. Nevertheless, after 40 months the patient developed two brain metastases. One was surgically resected and the smaller lesion was treated by gamma knife. Unfortunately, the patient died 42 months after the first presentation. Conclusively, in very selected patients with synchronic liver metastasis, multimodal treatment including repeated surgery, TACE and chemotherapy may prolong survival.